Badanie satysfakcji klienta czynnikiem warunkującym identyfikację atrybutów satysfakcji klienta z produktu spożywczego - Nieżurawski, Lech; Pawłowska, Bożena (Customer Satisfaction Research - Factor Influencing Identification of Customer Satisfaction Attributes of Food Product, 2006)
This paper presents the findings of the authors' studies, the identification of the issue and estimated customer satisfaction attributes which influence the level of customer satisfaction of food products in coming from Polish food industry enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 165-171